Singapore's exchange rate management system - Maysami, Ramin Cooper (2013)
Traditionally, in an era of limited capital mobility, where the domestic financial markets were still relatively undeveloped, the Monetary Authority of Singapore (MAS) relied on direct control measures as main instruments of monetary policy.